Mechanisms of Rehabilitation and Training of the Disabled (Texas Journal of Medical Science, 2023)
The implementation of the main directions of rehabilitation and rehabilitation of the disabled involves the use of technical means for the rehabilitation of the disabled, the creation of the necessary conditions for the unhindered access of the disabled to social, engineering and transport infrastructure facilities. The article also provides information on the rehabilitation of disabled people and their families, the rehabilitation of disabled people.